Вы находитесь на странице: 1из 4

# ()

-
1.
:

1
= 0, xyz ( x, y z ).
x+ y+ z

{(1; 2; 5)} .

. 1000 ( x + y + z ) ,

## xyz ( x + y + z ) = 1000 . x + y + z < 30 , xyz > 30 . 1000

, 40 50.
, 1000 : 100, 125, 200, 250
500. (1; 2; 5).
2. , 0 < a < b , 2ab ln b < b2 a 2 .
a

1. y = 1

(0; + ) . ,
[a; b] ,
1 1 b a
a

(. ). ,
b

1 1
+
1 dx < a b (b a )
2
x

1
a

y=1

1
b

ln x a < b a
2ab
2

2ab ln b < b2 a 2 .

0 a

## 2. 2ab ln b < b2 a 2 (0 < a < b) a 2

a
b
t = ( t > 1 ). t 2 2t 1 > 0
a

t > 1 .
f (t ) = t 2 2t ln t 1 . f (1) = 0 , f (t ) = 2t 2t ln t 2 , f (1) = 0 , f (t ) = 2 2 .
t

t > 1 , t > 1
. t = 1 , t > 1 ,
t > 1 . , f (t ) t > 1 , ,
f (1) = 0 , f (t ) t > 1 .
3. , 0 , f ( x + ) = f ( x ) +
x \ . , f ( x )
.

x, x\.

g ( x + ) = f ( x + ) ( x + ) = f ( x ) + x = f ( x ) x = g ( x )

. g ( x ) = f ( x )

x \ , g ( x ) - . , f ( x )

- g ( x )

x.

4.
2, 3 6 . , .

: 1 .

-1-

. a, b c , S
, p , ra = 2 , rb = 3 , rc = 6
. ,
ra , rb , rc , , ,
.
S = pr , S = ( p a )ra , S = ( p b) rb , S = ( p c ) rc ,
1 + 1 + 1 = p a + p b + p c = 3 p (a +b+ c) = p = 1 , r = 1 .
ra rb rc
S
S
S
S
S
r

## 5. ABC, ACD ABD, A,

1:2, 1:1 1:2 ( A). ,
.
: 1 : 15 .
. ABCD , AK, AM,
AN ABC, ACD ABD,
A, PQR
E, F G (.
). AE : EK = AG : GN , EG & KN .
, KN & CD . , EG & CD , B
, EG & ( ACD ) . ,
PQR, EG,
ACD QR, EG, , ,
QR & CD . QR
F AM, Q R
CT ABC
AK S, AB T. AS = 2 AK ,

A
P
E

R
F

NQ

K
C

AE = 1 AK , E AS.
3

Q AC, P
AT AP : AB = 1 : 4 .
,
PQR 1:4, 1:2 1:2, ,
VAPQR
AP AQ AR
= 1 . , VAPQR = 1 .
=
= 111
VABCD
VBCDPQR 15

T
S
B

6. .
.

f ( x ) = x + 22 x > 0 .
x

x + 22 2 2 .
x

x ,
2 2 ; + ,

: (0; + ) .

-2-

. , , ,
x > 0 .
. x0 , x0 = 22 , .. x0 = 3 2 , f ( x0 )
x0

.
.

x+x+ 2 3 .
3
2 2 x2
2

x = 22 , .. x = 3 4 , , f ( x )
2

x + ,
f ( 3 4); + , .. 33 ; + .
2

7. ( ,
,
).
.

f ( x ) = x 1 + 6 x 3x 2 .

: [ 1; 2] .
1. [0; 2].
6 x 3x 2 = 3x 3,
4 x 2 8 x + 3 = 0,
3

3
x
f ( x ) = 1 +
, f ( x ) = 0

x= 3;
2

<
1
x
2
6 x 3x 2
0 < x < 2

(2)

f (0) = 1 , f 3 = 2 , f (2) = 1 . ,

[1; 2] .
: .
2. f ( x) [0; 2].
G
f ( x ) = x 1 + 3 2 x x 2 a{1; 3}
G
b{x 1; 2 x x 2 } . f ( x) ,
G
G
G G G G G G
a = 2 b = 1 . a b a b a b 2 f ( x) 2 .
G
2
G
a b , x 1 = 2 x x , x = 3 , 3 [0; 2] ,
2
2
1
3
G G
f ( x) a b = 2 .
G
G
a , b
G
G
, a b ,

, ( x 1 6 x 3 x 2 )
[0; 2] x = 0 . , f (0) = 1
f ( x) [0; 2].
: .

-3-

3. f ( x ) = x 1 + 3 1 ( x 1) 2 ,
1 x 1 1 . x 1 = sin , . g () = sin + 3 cos ,
2

;
2 2

f ( x) . g () = 2sin +
3

+ 5 ,
6

g () ; [1; 2] .
2 2
: . .
4. : a,
f ( x ) = a .

:
6 x 3 x 2 = ( a + 1) x

2 x x 2 = x + a +1 (*)

(*) [0; 2] , , , a + 1 0 .
a y = x + a +1 ,
3

y = 2 x x 2 (1; 0) , 1.
:
x 2 2 x + y 2 = 0,
( x 1) 2 + y 2 = 0,
y = 2 x x2

y 0
y 0.
y = x + a +1

y = 2 x x 2

(. ).

y
a +1
3

y = 2x x2

a +1
y= x + 0
3

O
1

2
y= x
3

a0 + 1

, a [1; a0 ] , a0 a,
y = x + a +1 y = 2 x x 2 .
3

y = x +
3

3
a0 +1
3

1 , , ABO = 30 , , OA = 1 ,
3

OB = (a0 + 1) 1 = 2 , a0 = 2 .
: . .

-4-